Negative Occasion Setting in Juvenile Rats - Meyer, Heidi C. (Behav Processes, 2016)
Prior findings indicate that adolescent rats exhibit difficulty using negative occasion setters to guide behavior compared to adult rats [12]. Here, additional groups of juvenile rats were trained in the same negative occasion setting procedure to further define the development of negative occasion setting. Beginning on either postnatal day (PND) 30, 40, or 50, rats received daily training sessions in which a tone was paired with food reinforcement on some trials, while on other trials a light preceded the tone and no reinforcement was delivered. We found that rats that began training on PND 50 required 10 training sessions to discriminate between the two types of trials, consistent with prior findings with young adult rats. Interestingly, rats in the PND 30 group (pre-adolescents) also required just 10 training sessions, in stark contrast to adolescent rats that began training on PND 35 (adolescents) and required 18 sessions [12]. Rats that began training on PND 40 (adolescents) also required more sessions than the PND 30 group. These data indicate that the development of negative occasion setting is non-linear and have direct bearing on understanding the behavioral and neural substrates that underlie suboptimal behavioral control in adolescents.